Financial development and economic growth: New evidence from Tunisia - Ben Jedidia, Khoutem (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2014)
This paper examined an empirical investigation of whether financial development can boost economic growth in Tunisia. We used an Autoregressive Distributed Lag method to assess the finance-growth relation taking private credit, value traded and issuing bank's securities on the financial market as financial development indicators.